COMSOL5 for engineers - Tabatabaian, Mehrzad (Mercury Learning and Information, 2016)
This updated edition covers COMSOL5 which now includes a revolutionary tool, the Application Builder. This component enables users to build apps based on COMSOL models that can be run on almost any operating system (Windows, MAC, mobile/iOS, etc.). Designed for engineers from various disciplines, the book introduces multiphysics modeling techniques and examples accompanied by practical applications using COMSOL5.x. The book provides a collection of examples and modeling guidelines through which readers can build their own models. Features: expands the Finite Element Method (FEM) theory and adds more examples from the original edition; outlines the new features in COMSOL5, the graphical user interface (GUI), and how to build a COMSOL app for models; and includes apps for selected model examples-with parameterization of these models. Features new and modified, solved model examples, in addition to the models provided in the original edition. --